Treating the obese diabetic. Issue 2 (March 2013) - Kenkre, Julia; Tan, Tricia; Bloom, Stephen
Type 2 diabetes and obesity are intimately linked; reduction of bodyweight improves glycemic control, mortality and morbidity. Treating obesity in the diabetic is hampered as some diabetic treatments lead to weight gain. Bariatric surgery is currently the most effective antiobesity treatment and causes long-term remission of diabetes in many patients. However, surgery has a high cost and is associated with a significant risk of complications, and in practical terms only limited numbers can undergo this therapy. The choice of pharmacological agents suitable for treatment of diabetes and obesity is currently limited. The glucagon-like peptide-1 receptor agonists improve glycemia and induce a modest weight loss, but there are doubts over their long-term safety. New drugs such as lorcaserin and phentermine/topiramate are being approved for obesity and have modest, salutary effects on glycemia, but again long-term safety is unclear. This article will also examine some future avenues for development, including gut hormone analogues that promise to combine powerful weight reduction with beneficial effects on glucose metabolism.